Standardization of a Videofluoroscopic Swallow Study Protocol to Investigate Dysphagia in Dogs. (27th February 2017) - Harris, R.A.; Grobman, M.E.; Allen, M.J.; Schachtel, J.; Rawson, N.E.; Bennett, B.; Ledyayev, J.; Hopewell, B.; Coates, J.R.; Reinero, C.R.; Lever, T.E.
Abstract : Background: Videofluoroscopic swallow study (VFSS) is the gold standard for diagnosis of dysphagia in veterinary medicine but lacks standardized protocols that emulate physiologic feeding practices. Age impacts swallow function in humans but has not been evaluated by VFSS in dogs. Hypothesis/Objectives: To develop a protocol with custom kennels designed to allow free‐feeding of 3 optimized formulations of contrast media and diets that address limitations of current VFSS protocols. We hypothesized that dogs evaluated by a free‐feeding VFSS protocol would show differences in objective swallow metrics based on age. Animals: Healthy juvenile, adult, and geriatric dogs (n = 24). Methods: Prospective, experimental study. Custom kennels were developed to maintain natural feeding behaviors during VFSS. Three food consistencies (thin liquid, pureed food, and dry kibble) were formulated with either iohexol or barium to maximize palatability and voluntary prehension. Dogs were evaluated by 16 swallow metrics and compared across age groups. Results: Development of a standardized VFSS protocol resulted in successful collection of swallow data in healthy dogs. No significant differences in swallow metrics were observed among age groups. Substantial variability was observed in healthy dogs when evaluated under these physiologic conditions. Features typically attributed to pathologic states, such as gastric reflux, were seen in healthy dogs. Conclusions and Clinical Importance: Development of a VFSS protocol that reflects natural feeding practices may allow emulation of physiology resulting in clinical signs of dysphagia. Age did not result in significant changes in swallow metrics, but additional studies are needed, particularly in light of substantial normal variation.